Can the industrial transformation and upgrading demonstration zones policy improve urban green technology innovation? An empirical test based on old industrial cities and resource-based cities in China - Bingnan Guo; Junjie Hu; Xinyan Guo (Frontiers in Environmental Science)
IntroductionWith industrial transformation and upgrading being essential to attaining sustainable growth, the pursuit of green development has grown in importance on a global scale.MethodsThis study employs a sample dataset from 2011 to 2021, utilizing the national Industrial Transformation and Upgrading Zones (ITUZ) policy interventions of 2017 and 2019 as a quasi-natural experiment. Employing a difference-in-differences approach, this paper investigates the impact and underlying mechanisms of these policies on green technology innovation, as well as their heterogeneity across different urban contexts.ResultsThe results indicate that the ITUZ policy substantially improves green technology innovation in the designated cities, a conclusion that persists across multiple robustness assessments. Subsequent mechanistic research reveals that financial development and the enhancement of industrial structures are essential avenues for the realization of green technology innovation. The heterogeneity study highlights the policy’s significant impact on green technology innovation in eastern cities, uniform demonstration zones, and old industrial cities.DiscussionThis study finishes with practical implications for policy design, indicating that it is essential to extract and share the beneficial experiences from pilot cities during the establishment of demonstration zones. It underscores the importance of synchronizing urban development policies with local characteristics to investigate varied and successful approaches for advancing green technology innovation. This research offers critical insights for policymakers and urban planners in guiding the transition of older industrial and resource-based cities toward a more sustainable and environmentally friendly future.